Commercial Transaction in Sri Lanka’s Digital Economy: A Critical Analysis - Christian, M.D.A. (Faculty of Arts, University of Jaffna & Surana and Surana International Attorneys, 2026)
The rapid emergence of digital technologies has fundamentally transformed how commercial transactions are conducted, creating opportunities for efficiency, innovation, and market expansion, while simultaneously exposing significant limitations in traditional commercial law frameworks. This study critically analyses the evolving legal landscape governing commercial transactions in Sri Lanka’s digital economy. The primary objectives are to examine how digitalisation has altered the nature of commercial transactions, to identify legal challenges posed by digital contracts, digital payments, and online market places, to evaluate the effectiveness of existing commercial laws, and to propose legal and policy reforms necessary to update the regulatory framework. Drawing on key statutes, including the Electronic TransactionsbAct No. 19 of 2006, the Payment and Settlement Systems Act No. 28 of 2005, the Consumer Affairs Authority Act No. 9 of 2003, and the Personal Data Protection Act No. 9 of 2022, this research employs a critical legal analysis methodology to interrogate current legislative provisions and their application in practice. The findings reveal that while Sri Lanka’s commercial law provides a foundational legal structure to accommodate digital economic activities, significant gaps and challenges persist. For example, despite the Electronic Transactions Act’s recognition of electronic contracts and signatures, issues around cross-border enforceability, consumer protection in digital settings, and the regulation of emerging technologies remain underaddressed. Furthermore, digital payment systems and data protection mechanisms require stronger integration to safeguard users and enhance trust in online transactions. The study highlights that existing statutes are often fragmented and do not cohesively address the velocity and complexity of digital commerce. Consequently, legal uncertainty and regulatory ambiguity continue to pose risks for businesses and consumers alike. To modernise commercial law for the digital era, this research advocates for comprehensive reform that includes updating contract law principles to expressly cover smart contracts and automated transactions, strengthening consumer rights in digital marketplaces, harmonising data protection norms with global best practices, and enhancing regulatory oversight of digital payment infrastructures. Such reforms are crucial to closing regulatory gaps, promoting legalclarity, and supporting the sustainable growth of Sri Lanka’s digital economy.
Keywords: Digital economy; Electronic transactions; Commercial law reform; Digital; Contracts; Legal certainty